Emerging adults facing the risk of professional and educational inactivity - Anna Walczak (Studia z Teorii Wychowania, 2025)
The article addresses the issue of emerging adults' transition from the educational system to the labour market. This issue is part of the consideration of the trajectories of entry into adulthood, which in the era of late modernity lose their linear character, lengthen, become fragmented and reversible. Particular attention was paid to those who fall into the NEET (neither in employment, education, nor training) category, whose situation can be considered as one variant of the trajectory of the transition to adulthood. The empirical basis is survey research on a random, nationwide sample of people aged 18-29 (n=330), stratified by gender and education. The analysis aims to answer questions about educational plans, differences between those who fall into the NEET category and economically and educationally active emerging adults, and factors co-occurring with educational and labour inactivity. The results indicate the importance of low cultural and economic capital and rural residence in raising the risk of entering the NEET category. Polish emerging adults pursuing the NEET model appear to be Mertons’ withdrawers rather than rebels.